Pementaan dan faktor risiko sosioekonomi dan perilaku terhadap kejadian penyakit periodontal di kecamatan pundong kabupaten bantul - Prayudha Benni Setiawan; Hartono Hartono; Regina Titi Christinawati Tandelilin; Bekti Nur'aini (Universitas Gadjah Mada, 2020)
Periodontal disease is pathological damage that affects the tooth supporting tissues. Systemic conditions largely influence its pathogenesis. Besides, environmental, socioeconomic, behavioural, environmental and geographic factors can affect individuals experiencing periodontal disease. Geographic Information System (GIS) can be used to analyze the differences of these factors, especially those relating to geographic differences, demographic factors, social, etc. Pundong district has geographical and socio-economic variation. This study aims to describe the distribution of patients with periodontal disease based on socioeconomic and behavioral factors. The type of study was an observational analytic survey with a cross-sectional design. The subject of research is determined by Registry Based Study approach where Pundong Community Health Center as the primary data source in this research. Independent variable is periodontal disease, while the dependent variable is a socioeconomic factor and health behaviour. Overview of periodontal disease mapping using ArcGIS, with an overlay method or combining two layers, namely the administrative map of Pundong District and coordinates of patients with periodontal disease. Univariate and bivariate analysis using Stata to analyze the distribution and the relationship of each variable. Generalized periodontitis often occurs in Seloharjo. Seloharjo has the most deprived people in Pundong Sub-district. The variables significantly associated with periodontal disease severity were economic status and brushing behaviour (p-value <0.05).